Bilateral Tonsillar Kaposi Sarcoma: A Rare Finding. (21st September 2018) - Booth, Adam; Yassi, Usama; Qiu, Suimin
Abstract: Kaposi sarcoma (KS) is a vascular proliferative neoplasm consistently associated with human herpesvirus 8 (HHV-8) infection in immunocompromised patients. We report a case of a 51-year-old male with a history of human immunodeficiency virus (HIV)/AIDS not on antiretroviral therapy, recurrent KS over 10 and 5 years previously, successfully treated with multiple cycles of liposomal doxorubicin. On presentation, the patient complained of mild hoarseness, dysphagia, and a 2-month history of enlarging cervical lymph nodes. Computed tomography showed an irregular, enhancing mass in the left palatine tonsil extending into the base of the tongue and left uvula with multiple enlarged, enhancing cervical lymph nodes and bilateral necrotic intraparotid lymph nodes. Laryngoscopy demonstrated a purple mass at the region of the left tonsil. The patient underwent bilateral tonsillectomy without complications. Gross examination of the specimens revealed a disproportionately enlarged left tonsil compared to the right with grossly unremarkable cut surfaces. Microscopically, the left tonsil revealed a 2.0-cm submucosal lesion containing fascicles of spindle-shaped endothelial cells with characteristic slit-like vascular spaces and extravasated erythrocytes. Immunohistochemistry performed for HHV-8 was positive, confirming the diagnosis of KS. Careful microscopic examination of the right tonsil revealed an additional 0.2-cm focus of KS. Diagnosis is considered an AIDS-defining illness and almost always arises in patients with low CD4 T-cell counts. AIDS-associated KS is a more aggressive form of KS as HIV infection augments HHV-8 replication. Importantly, this form may flare or regress dependent on antiretroviral therapy. KS originating in head and neck mucosal sites is uncommon in itself. Bilateral lesions in the tonsils are very rare, and small foci may not be seen on imaging. This case highlights the need for increased awareness of this rare site of involvement among pathologists, infectious disease specialists, and surgeons.